PERANAN PENGAWAS SEKOLAH DALAM MENGOPTIMALISASI KOMPETENSI GURU SEKOLAH DASAR MENGIMPLEMENTASI KURIKULUM 2013 - Marselinus Robe (JIPD (Jurnal Inovasi Pendidikan Dasar), 2017)
This writing explores the role of school supervisor in improving teachers’ competence in the implementation of 2013 curriculum. The implementation of 2013 curriculum is not free from any problem. Lack of teachers’ knowledge and experience is one of the obstaclesin implementing 2013 curriculum. Therefore, this situation requires the role of school supervisor in assisting and guiding teachers in classrooms.